Barriers and facilitators impacting the implementation of digital interventions targeted at mental health and musculoskeletal disorders in the workplace: a scoping review protocol - Mallorie Leduc; Andrea Sinesi; Margaret Kenneally; Margaret Maxwell; Birgit Greiner; Birgit Aust; Carolina Piña; Andreas Czaplicki; Evelien Coppens; Alex Burdorf; Ricardo Gusmão; Daniel Guinart; et al. (Systematic Reviews)
Abstract Background The digital transition in the workplace has increased trends such as permanent connectivity, an increased sedentary lifestyle, and reduced social interaction, leading to additional psychosocial and ergonomic risks for workers. Musculoskeletal disorders (MSDs) and mental health problems are particularly prevalent, posing a significant burden. To address these challenges, organisations can implement digital or blended interventions targeting MSDs and mental health problems. However, there is still limited evidence on combined workplace interventions targeting both MSDs and mental health problems and respective facilitators and barriers for their successful implementation and sustainability. The objective of this scoping review is to identify barriers and facilitators to the implementation of blended and digital interventions targeted at combined mental health and MSDs in the workplace. Methods Bibliographic databases will be searched for studies published since 2014 and reported on the implementation of interventions with a digital component targeted at mental health and MSDs in the workplace. Studies will be included if the intervention was delivered within, or access provided through, the workplace. The title and abstract screen and the full-text screening will be completed independently by two reviewers, with a third reviewer resolving any arising conflicts in the process. Results Descriptive characteristics of the study design, workplace sector, mode of working, intervention details, mode of intervention delivery, outcomes, and barriers and facilitators will be extracted. Results will be reported in accordance with the PRISMA for Scoping Reviews checklist and a narrative synthesis used to summarise characteristics of included studies, as well as barriers and facilitators to the implementation of interventions. Discussion The findings from this review will provide practical recommendations relevant to researchers and practitioners developing or implementing digital interventions in the workplace targeting mental health conditions and MSDs. Systematic review registration Research Registry, reviewregistry1847, https://www.researchregistry.com/browse-the-registry#registryofsystematicreviewsmeta-analyses/registryofsystematicreviewsmeta-analysesdetails/66671b683a0f410028a230bd/ .